A Parent and Student Guide to the ABC’s of Norm and Criterion Reference Testing - Allanson, Patricia Bolton; Allanson, Patricia Bolton; Rawlings, Robin; Rawlings, Robin; Notar, Charles E. (Advances in Social Sciences Research Journal, 2017)
It has been stated that one year of a students primary and secondary education is used for testing. The importance of having a full understanding of the types of standardized tests millions of students will experience can not be understated. Since the mid 1800’s, standardized testing has been part of American education. Specifically, educators use norm and criterion referenced testing as part of their profession. Parents and students need to understand what these tests mean, specific differences, and how they bear upon their lives. Although teachers use these tests to make judgments, the students and parents must understand the results of norm and criterion referenced assessments. The following is a guide assembled by the authors to help in that understanding those results. The authors have a combined 100 years of experience in education at the high school, junior college and university level (Reynolds, et al., 2006)..